Indications for the Use of Local Protective Factors in Patients Treated for Phlegmoma of the Maxillofacial Region (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article is devoted to the clinical effectiveness of complex treatment of phlegmon of the facial region in patients with liver pathology. Prevention and treatment of infectious diseases in the field of surgery is one of the most important tasks facing modern dentistry. According to literature data, more than 54% of surgical complications of odontogenic infection are associated with concomitant pathology - cardiovascular and respiratory diseases, diabetes mellitus, kidney and liver diseases.